Care and communication between health professionals and patients affected by severe or chronic illness in community settings: a qualitative study of care at the end of life - Pollock, Kristian; Wilson, Eleanor (NIHR Health Technology Assessment Programme, 2015)
Background: Advance care planning (ACP) enables patients to consider, discuss and, if they wish, document their wishes and preferences for future care, including decisions to refuse treatment, in the event that they lose capacity to make decisions for themselves. ACP is a key component of UK health policy to improve the experience of death and dying for patients and their families. There is limited evidence about how patients and health professionals understand ACP, or when and how this is initiated. It is evident that many people find discussion of and planning for end of life care difficult, and tend to avoid the topic. Aim: To investigate how patients, their relatives and health professionals initiate and experience discussion of ACP and the outcomes of advance discussions in shaping care at the end of life. Design and data collection: Qualitative study with two workstreams: (1) interviews with 37 health professionals (general practitioners, specialist nurses and community nurses) about their experiences of ACP; and (2) longitudinal case studies of 21 patients with 6-month follow-up. Cases included a patient and, where possible, a nominated key relative and/or health professional as well as a review of medical records. Complete case triads were obtained for 11 patients. Four cases comprised the patient alone, where respondents were unable or unwilling to nominate either a family member or a professional carer they wished to include in the study. Patients were identified as likely to be within the last 6 months of life. Ninety-seven interviews were completed in total. Setting: General practices and community care settings in the East Midlands of England. Findings: The study found ACP to be uncommon and focused primarily on specific documented tasks involving decisions about preferred place of death and cardiopulmonary resuscitation, supporting earlier research. There was no evidence of ACP in nearly half (9 of 21) of patient cases. Professionals reported ACP discussions to be challenging. It was difficult to recognise when patients had entered the last year of life, or to identify their readiness to consider future planning. Patients often did not wish to do so before they had become gravely ill. Consequently, ACP discussions tended to be reactive, rather than pre-emptive, occurring in response to critical events or evidence of marked deterioration. ACP discussions intersected two parallel strands of planning: professional organisation and co-ordination of care; and the practical and emotional preparatory work that patients and families undertook to prepare themselves for death. Reference to ACP as a means of guiding decisions for patients who had lost capacity was rare. Conclusions: Advance care planning remains uncommon, is often limited to documentation of a few key decisions, is reported to be challenging by many health professionals, is not welcomed by a substantial number of patients and tends to be postponed until death is clearly imminent. Current implementation largely ignores the purpose of ACP as a means of extending personal autonomy in the event of lost capacity. Future work: Attention should be paid to public attitudes to death and dying (including those of culturally diverse and ethnic minority groups), place of death, resuscitation and the value of anticipatory planning. In addition the experiences and needs of two under-researched groups should be explored: the frail elderly, including those who manage complex comorbid conditions, unrecognised as vulnerable cases; and those patients affected by stigmatised conditions, such as substance abuse or serious mental illness who fail to engage constructively with services and are not recognised as suitable referrals for palliative and end of life care.